Are CDI Systems Multicolored, Facultative, Helping Greenbeards?. Issue 5 (May 2017) - Danka, Elizabeth S.; Garcia, Erin C.; Cotter, Peggy A.
Abstract : Competitive and cooperative interactions between organisms, including bacteria, can significantly impact the composition of a community and the fitness of its members, as well as the fitness of their hosts when communities are living on or within other organisms. Understanding the underlying mechanisms is critical to the development of strategies to control microbiological communities that impact animal and plant health and also for understanding the evolution of social behaviors, which has been challenging for evolutionary biologists. Contact-dependent growth inhibition (CDI) is a phenomenon defined by the delivery of a protein toxin to the cytoplasm of neighboring bacteria upon cell–cell contact, resulting in growth inhibition or death unless a specific immunity protein is present. CDI was first described based on observations of interbacterial killing and has been assumed to function primarily as a means of eliminating competitor cells. However, recent molecular evidence indicates that multiple levels of specificity restrict CDI toxin delivery and activity to the same bacterial strain, and that CDI system proteins can mediate cooperative behaviors among 'self' cells, a phenomenon called contact-dependent signaling (CDS). Here we review these recent findings and discuss potential biological and evolutionary implications of CDI system-mediated interbacterial competition and cooperation. Trends: Specificity between BcpA/CdiA proteins and receptors and translocator proteins restricts delivery of BcpA-CT/CdiA-CT polypeptides to closely related bacteria. In Burkholderia thailandensis, delivery of BcpA-CT into an immune cell results in a change in gene expression, a phenomenon called contact-dependent signaling (CDS). CDI system-encoding genes are located on genomic islands. CDI system-encoding genes are tightly regulated. In B. thailandensis, these genes are expressed stochastically; they are expressed highly in 0.1% of cells growing in culture or in a biofilm. bcpAIOB genes act as both helping and harming greenbeards; they induce gene expression changes in 'self' bacteria that cause cooperative behaviors and inhibit the growth of, or kill, 'non-self' bacteria. As multicolored, facultative, helping greenbeards, CDI/CDS systems represent an excellent model for studying social evolution.